Pengembangan Knowledge Management Solution Untuk Monitoring Mutu Pada Rumah Sakit Kartika Pulomas Jakarta - Azis Sukma Dhiana (LPPM Universitas Bina Sarana Informatika, 2019)
Knowledge is crucial to an organization to enhance the competitive capabilities in the face of obstacles and challenges in carrying out the tasks. If knowledge isn’t properly managed then knowledge may be lost or not use efficiently. The effect for not managing knowledge will impact to people, process, product or organization performance (Fernandez, 2010). Scattered knowledge and difficult to use is a constraint contained in Kartika Pulomas Hospital. This research is focus on creating a knowledge management solution that can be used for quality indicator, Kartika Pulomas Hospital that has issue with knowledge management. To support the knowledge management solution, a prototype of knowledge management system is also implemented. This research is conducted by using the methodology of designing knowledge management solution from Fernandez and also Unified Software Development Process (USDP) methodology to design the knowledge management system. The results of this research are priority for the development of Knowledge Management Solution and knowledge management system design model that needed by Kartika Pulomas Hospital